The synthesis and characterization of 1,2-dihydroxyimino-3,6-di-aza-8,9-O-iso-butylidene nonane and its complexes with Ni(II), Cu(II), Zn(II) and Cd(II) - Canpolat, E; Kaya, M; Görgülü, AO (Polish Chemical Society, 2002)
1,2-Dihydroxyimino-3,6-di-aza-8,9-O-iso-butylidene nonane (H2L) was synthesized starting from 1,2-O-iso-butylidene-4-aza-6-amino hexane (RNH2) and antichloroglyoxime. Ni(II) and Cu(II) complexes of H2L have a metal:ligand ratio of 1:2 and the ligand coordinates through two N atoms, as do most of the vic-dioximes. However, Zn(II) and Cd(II) complexes of H2L have a metal:ligand ratio of 1:1 and one chloride ion and one water molecule are also coordinated to the metal ion. Structures of the ligand and its transition-metal complexes are proposed, according to elemental analyses, IR, C-13 and H-1 NMR spectra, magnetic susceptibility measurements and thermogravimetric analyses (TGA).
Keywords: vic-dioxime; Ni(II); Cu(II); Zn(II); Cd(II) complexes